Method of evaluating the expected reliability of applied computer programs of medical electronics systems - S. M. Borovikov; S. S. Dick (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The authors propose a method for estimating the expected reliability of applied computer programs for medical computer systems in the early stages of their design. To obtain the expected operational reliability of a computer program, the method uses correction factors that take into account the most important factors determining the initial level of program reliability (before testing begins). Accounting for the impact on the reliability of the program testing procedures are performed using a correction factor that depends on metrics that take into account testing technology, testing time, experience and qualifications of specialists.